2021
DOI: 10.2147/dddt.s296548
|View full text |Cite
|
Sign up to set email alerts
|

EGCG Regulates Cell Apoptosis of Human Umbilical Vein Endothelial Cells Grown on 316L Stainless Steel for Stent Implantation

Abstract: Background: Nowadays, medical grade 316L stainless steel (316L SS) is being widely used for intravascular stents, and the drug-eluting stent (DES) system is able to significantly reduce the occurrences of in-stent restenosis. But the drugs and the polymer coating used in DES potentially induce the forming of late stent thrombosis. In order to reduce the occurrence of ISR after stent implantation, the development of novel drugs for DESs is urgently needed. Methods: This study aimed to investigate the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Thus, multiple lines of evidence from animal models suggest that EGCG exhibits a wide range of neuroprotection to improve various neurological disorders, such as ischemic stroke, Huntington’s, and Alzheimer’s diseases [ 1 , 11 , 12 ]. Meanwhile, research reveals that EGCG is capable of improving ROS-mediated oxidative stress and inflammatory responses so as to effectively reduce further oxidative injury in rats with spinal cord injury [ 1 , 2 , 3 ]. Another animal study indicates neurological diseases of contusive spinal cord injury and neuropathic pain can be mitigated by EGCG therapy [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, multiple lines of evidence from animal models suggest that EGCG exhibits a wide range of neuroprotection to improve various neurological disorders, such as ischemic stroke, Huntington’s, and Alzheimer’s diseases [ 1 , 11 , 12 ]. Meanwhile, research reveals that EGCG is capable of improving ROS-mediated oxidative stress and inflammatory responses so as to effectively reduce further oxidative injury in rats with spinal cord injury [ 1 , 2 , 3 ]. Another animal study indicates neurological diseases of contusive spinal cord injury and neuropathic pain can be mitigated by EGCG therapy [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epigallocatechin gallate (EGCG) is a natural compound that mainly exists in fruits and plants to protect against environmental stress [ 1 ]. The rat model displays that EGCG possesses the beneficial properties of anti-inflammation and anti-oxidation [ 1 , 2 , 3 ]. Therefore, EGCG has been shown to exert neuroprotective efficacies that result in increased numbers of neurons and the recovery of motor functions in spinal cord injury and sciatic nerve crush injuries [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shin-ichiro et al showed that endothelial autophagy differentially induced by sirolimus and paclitaxel via regulating LC3B, Bcl-2, and p53 was one of the potential mechanisms in suppressing re-endothelialization and revascularization, as well as NO production in human aortic ECs [130]. In addition, epigallocatechin-3-gallate (EGCG) and nickel-containing austenitic 316L stainless steel (316L SS) were reported to inhibit human umbilical vein EC (HUVECs) proliferation by upregulating the autophagic genes ATG 5/7/12 and the cell apoptosis genes caspase 3/8/9 and Fas to suppress the occurrence of ISR [131,132]. Moreover, autophagy-dependent endothelial membrane remodeling is crucial for rapamycin-eluting stent-induced stent thrombosis [133].…”
Section: Autophagy In Percutaneous Coronary Intervention (Pci)-associ...mentioning
confidence: 99%
“…The following supporting information can be downloaded at: https: //www.mdpi.com/article/10.3390/cells11132081/s1, Table S1: Mechanistic studies implicating endothelial autophagy or mitophagy in cardiovascular diseases [93,105,106,[108][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126][130][131][132][133][149][150][151][152][153][154][155][156][157][158][159][160][166][167][168][169][170]181,[184][185][186][187]…”
Section: Supplementary Materialsmentioning
confidence: 99%